Survey on optimum planting spacing with three leguminous species in rain fed system (pure and mixed) on sandy hills of Khouzestan, Iran - Mohammad Hasan Saleheh Shooshtari; Manoochehr Amani; Koorosh Behnamfar; Seddigheh Naanaie (تحقیقات جنگل و صنوبر ایران, 2008)
In order to select the optimum interplant distance and determination the best species for biological sand dune fixation, this study was carried out on sandy hills of  (Khouzestan province) located in southwest of Iran. There are about 350,000 ha of sandy dunes and sandy lands in Khouzestan. During the past 40 years, different physical, chemical and biological operations were applied to stabilize these lands and the results were all satisfied. This experiment was conducted in 1999 under rain fed conditions and statistical method of split plots and Fully Randomized Design Complete Blocks, with three replicates. The main treatments consisted of three levels of spacing (3×3m, 4×4m and 5×5m), and the secondary treatments consisted of three species (Prosopis juliflora, Acacia victoriae and A. farnesiana) in form of pure and mixed(50%) in six levels. The measured characteristics were: survival, mean height, crown diameter and the effect of interplant distance. In this study, a petroleum mulch cover was applied to stabilize the sandy dunes against wind erosion. After five years, the data were analyzed. The results showed that the greatest survival rate belonged to the species of P.juliflora and A.victoriae with 73 and 62 percent, respectively. The species of P.juliflora attained to the highest mean height in pure plantation with 4.9 meter followed by A.victoriae and A.farnesiana with 3.69 and 1.84 meters respectively. The highest crown diameter (5.28 m) achieved by P.juliflora in mixed plantation with A.farnesiana and the least (1.9 m) in all treatments was measured by A. farnesiana.